2018
DOI: 10.1186/s40623-018-0827-3
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic and postseismic deformation associated with the 2016 Mw 7.8 Kaikoura earthquake, New Zealand: fault movement investigation and seismic hazard analysis

Abstract: The 2016 moment magnitude (Mw) 7.8 Kaikoura earthquake demonstrated that multiple fault segments can undergo rupture during a single seismic event. Here, we employ Global Positioning System (GPS) observations and geodetic modeling methods to create detailed images of coseismic slip and postseismic afterslip associated with the Kaikoura earthquake. Our optimal geodetic coseismic model suggests that rupture not only occurred on shallow crustal faults but also to some extent at the Hikurangi subduction interface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
1
9
0
2
Order By: Relevance
“…One of the outstanding questions surrounding the Kaikōura earthquake concerns the interaction of upper plate faults with the underlying subducted plate. Time‐dependent inversions of GPS and InSAR data suggest widespread triggering of slow‐slip events on the Hikurangi subduction interface beneath the North Island and large (~0.5 m) afterslip on the subduction interface directly beneath the rupture area (Jiang et al, ; Wallace et al, ). Wallace et al () showed that the large‐scale postearthquake deformation in the South Island can be explained by displacement on the subduction interface, with the primary patch at 40‐km depth down‐dip from the Kaikōura earthquake region, and a smaller patch extending to 25‐km depth directly under the southern part of the rupture.…”
Section: Discussionmentioning
confidence: 99%
“…One of the outstanding questions surrounding the Kaikōura earthquake concerns the interaction of upper plate faults with the underlying subducted plate. Time‐dependent inversions of GPS and InSAR data suggest widespread triggering of slow‐slip events on the Hikurangi subduction interface beneath the North Island and large (~0.5 m) afterslip on the subduction interface directly beneath the rupture area (Jiang et al, ; Wallace et al, ). Wallace et al () showed that the large‐scale postearthquake deformation in the South Island can be explained by displacement on the subduction interface, with the primary patch at 40‐km depth down‐dip from the Kaikōura earthquake region, and a smaller patch extending to 25‐km depth directly under the southern part of the rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Both the largest Kaikoura earthquake dextral slips (up to 12 m at surface 11,17 ), and the abrupt rupture arrest occurred at the northeastern tip of the Needle fault system 18 , situated ~35 km away from the southern end of the WP fault 11 . The Kaikoura earthquake thus increased the stress loading on the southern WP 11,[19][20][21] as evidenced by the significant post-seismic deformation observed across the WP fault 20 . Together these may contribute to bringing the WP fault closer to failure.…”
mentioning
confidence: 99%
“…An earthquake rupture is a process of releasing and readjusting stress; accordingly, stress readjustment plays an important role in understanding the seismic hazard in a seismogenic region, as has been reported by many studies [12,32,44,45]. Without taking shallow slip into account, the distributed slip model of the 2018 Hokkaido eastern Iburi earthquake evaluated herein was used to calculate the static Coulomb stress change (∆CSC) on the fault plane and in the periphery of the study region using Coulomb 3.3 software [46,47], in order to understand the transfer of stress from deep to shallow depths and assess the regional seismic hazards.…”
Section: Static Coulomb Stress Changes and Seismic Hazardsmentioning
confidence: 95%